“TERPI” AS A QUANTITY OF THERMODYNAMIC POTENTIAL ENERGY SUPPLEMENTARY TO THE CONCEPT OF WORK AND HEAT - RHA Sahirul Alim (Universitas Gadjah Mada, 2003)
Isothermal reversible thermodynamic processes were studied, where there will not occur flow of heat (q) in the system in accord with the second law of thermodynamic. It appear that the energy flow in the system cannot be explained adequately by considering the flow of P,V - work, usually indicated by w, in accordance with the first law, that is, ΔU = q + w with q = 0. Therefore, it is necessary to have another kind of work energy (potential) which is not electrical to explain such as the experiment of Boyle that results in the formula PV = C for a close ideal gas system undergoing an isothermal and reversible process. In this paper, a new work potential which is called